2016
DOI: 10.3389/fpubh.2016.00067
|View full text |Cite
|
Sign up to set email alerts
|

Education and Alcohol Consumption among Older Americans; Black–White Differences

Abstract: PurposeAlthough the link between education and alcohol consumption is known, limited information exists on racial differences in this link. We conducted the current study to test Black–White differences in the association between education and alcohol consumption among older adults in the U.S.MethodsThis cross-sectional survey enrolled 1,493 Black (n = 734) and White (n = 759) older adults (age 66 or more) in U.S. Data came from the Religion, Aging, and Health Survey, 2001. Race, demographics, socioeconomics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
180
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 139 publications
(205 citation statements)
references
References 69 publications
25
180
0
Order By: Relevance
“…As previously suggested, these studies have consistently found smaller health benefits from access to social resources and possession of certain assets for Blacks compared to Whites. These findings seem to hold across developmental phases, as they are observed among young people (Assari, Thomas, Cadlwell, & Mincy, ), adults (Assari & Lankarani, ), and older adults (Assari & Lankarani, ).…”
Section: Differential Effects Versus Differential Exposuresmentioning
confidence: 66%
“…As previously suggested, these studies have consistently found smaller health benefits from access to social resources and possession of certain assets for Blacks compared to Whites. These findings seem to hold across developmental phases, as they are observed among young people (Assari, Thomas, Cadlwell, & Mincy, ), adults (Assari & Lankarani, ), and older adults (Assari & Lankarani, ).…”
Section: Differential Effects Versus Differential Exposuresmentioning
confidence: 66%
“…Other researchers have found ethnic and gender differences in health gains associated with SES indicators such as education [2,4244,6468]. Ethnicity [47], gender [2,45,69] and their intersection [45,49,50] may alter health gain associated with SES.…”
Section: Discussionmentioning
confidence: 99%
“…The intersection of race and gender may also modify the shape and also the mechanisms by which SES protects health outcomes [42]. Thus, rather than as control variables, race, ethnicity, and gender should be conceptualized as effect modifiers [44]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, highly educated Black and Hispanic people were found to be exposed to high levels of second-hand smoke exposure [33]. In addition, highly educated Blacks and Hispanics are more likely to drink alcohol [15,34], smoke cigarettes [18,35], and vape e-cigarettes [36]. This is probably why highly educated Black and Hispanic individuals may be at a higher risk of a wide range of non-communicable diseases such as hypertension [37], chronic obstructive pulmonary disease (COPD) [29] Some of the mechanisms behind these MDRs include societal and structural processes and factors such as residential segregation, extra costs of moving upward in the society [38,39], and a higher level of exposure [8,40,41] and sensitivity to discrimination [42] in ethnic minorities, particularly Blacks.…”
Section: Introductionmentioning
confidence: 99%